AB0006 Microrna expression profiles in peripheral blood mononuclear cells of early rheumatoid arthritis. (23rd January 2014) - Ciancio, G.; Ferracin, M.; Zagatti, B.; Saccenti, E.; Farina, I.; Bagnari, V.; Trotta, F.; Negrini, M.; Govoni, M.
Abstract : Background: Rheumatoid arthritis(RA) is a chronic inflammatory joint disorder characterized by immune-driven inflammation of synovial membrane which results in erosion, joint destruction and disability. The etiology of RA is still unknown and many uncertainties regarding its pathogenetic mechanisms persist. Micro-RNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression. Emerging evidence has linked mi-RNA altered expression with pathogenic mechanisms of neoplastic and more recently autoimmune and rheumatic diseases, including RA. Moreover, in the field of rheumatic diseases, miRNAs are today a new exciting area of research as potential biomarkers. Many recent studies have demonstrated that different miRNAs are significantly disregulated (up- or down-regulated) in peripheral blood mononuclear cells (PBMC) and/or synovial cells from RA when compared with healthy controls or osteoarthritis (OA). Of particular interest are today considered miR-155 and miR-146a, which have been found up-regulated both in RA synovial tissue and PBMC, and miR-223, which has been found up-regulated in RA T-lymphocytes from peripheral blood. Objectives: Our purpose was to verify whether specific miRNAs are differentially modulated in very early RA in comparison with healthy controls. Methods: Blood samples from 10 consecutive patients with early and naïve from any treatment RA (disease duration in months: 2±1, 4; M:5; F:5; mean age: 57, 8±0, 48 ) were collected. All patients fulfilled the 2010 ACR/EULAR criteria for RA classification and had active disease (DAS28: 5, 34 ± 0, 48). 8/10 patients were rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) antibodies positive. As controls, 12 random healthy volunteers (M:4; W:8; mean age 34 ± 11) were recruited. The expression levels of 723 mature miRNAs in peripheral blood mononuclear cells (PMBC) were investigated in all patients and controls by using Agilent miRNA microarray. Hybridization and data analysis was performed as already described. Differentially expressed genes were identified by using GeneSpring GX software (Agilent Technologies) and moderated t-test with p<0.05. Results: We identified 23 microRNAs significantly upregulated in RA patients ( p<0.005 ) compared to healthy controls. Among these, miR-21-3p appeared of special interest because of the extent of its modulation and its biological significance. MiR-146a, miR-155 and miR-223 resulted not up-regulated in PBMCs of our early-RA patients in comparison with controls. Conclusions: A 23-miRNA signature was identified in patients with early active RA. These data seem to confirm that some miRNAs could have important implications in reflecting the underlying pathogenic processes of RA. Moreover, their expression in patients with active and early disease makes them attractive as potential biomarkers of disease. However, more studies on larger series in patients naïve from treatmentare needed in order to identify miRNA specifically correlated to RA. Disclosure of Interest: None Declared